Unveiling the Circular Economy's Impact on Organizational Performance and Reputation - Rahman, Mahmudur (Global journal of Business and Integral Security, 2024)
This thesis examines how the circular economy affects organizational performance and reputation by analyzing firms' environmental sustainability initiatives in different sectors. The study uses both quantitative analysis and qualitative narratives to gain a thorough grasp of the topic matter, employing a mixed-method approach. The research analyzes firms' environmentally friendly efforts, such as circular design and the adoption of renewable energy, to lay the groundwork for assessing the impact of sustainability-focused strategies in business models and how circular principles alter organizational cost structures, bolstering economic sustainability and adaptability. The survey results emphasize the economic benefits of incorporating sustainability, such as lower manufacturing costs, improved resource efficiency, and waste reduction and trajectories of how organizations use circular processes to reduce expenses, enhance brand image, and increase profitability. The study reveals a complex range of organizational reactions to sustainability efforts, with most reporting positive results but a significant portion noting neutral or negative impacts. Ultimately, the research highlights the significance of aligning strategic goals and being able to adjust to different pressures to achieve economic resilience through circular behaviors. It highlights the interdependence between sustainability efforts, stakeholder views, and organizational effectiveness. The implications point towards potential competitive advantage by embracing the circular economy principles can help organizations differentiate themselves from competitors by demonstrating their commitment to sustainability and responsible resource management. The thesis promotes a constant commitment to sustainability, encouraging firms to adopt innovation, resilience, and a holistic perspective. It motivates upcoming scholars, professionals, and decision-makers to investigate and create new ideas for a circular and sustainable future to mitigate risks associated with resource scarcity, regulatory changes, and shifting consumer preferences towards sustainable products.